2019
DOI: 10.4067/s2452-45492019000100042
|View full text |Cite
|
Sign up to set email alerts
|

Ligadura interesfinteriana del trayecto fistuloso (LIFT) como alternativa de tratamiento a una fístula perianal compleja

Abstract: Ligation of intersphincteric fistula tract (LIFT) as an alternative treatment for complex perianal fistula. Introduction: Surgical techniques for complex perianal fistula have high recurrence and fecal incontinence rates. The technique of LIFT (ligation of the intersphincteric fistula tract) has achieved lower rates of recurrence with almost no risk of incontinence according to international reports. However, it is not yet consolidated as a standard technique for this pathology. Objective: To present the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Thus, to obtain a more fibrous and consistent tract, some authors have suggested the placement and maintenance of a non-cutting seton for a few weeks prior to the definitive ligation of the fistulous tract. 15,[21][22][23] However, some studies question the idea of the seton favoring the development of a more consistent fistulous tract path. 7,24 Furthermore, in the original series of Rojanasakul, with more than 250 patients, the use of a previous seton was not mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to obtain a more fibrous and consistent tract, some authors have suggested the placement and maintenance of a non-cutting seton for a few weeks prior to the definitive ligation of the fistulous tract. 15,[21][22][23] However, some studies question the idea of the seton favoring the development of a more consistent fistulous tract path. 7,24 Furthermore, in the original series of Rojanasakul, with more than 250 patients, the use of a previous seton was not mentioned.…”
Section: Discussionmentioning
confidence: 99%